Genetic regulation of membrane trafficking, exosome secretion, growth and dense-core granule biogenesis in the Drosophila accessory gland - Redhai, S (2018)
Many epithelial cell types, particularly those in glands, employ distinct regulated and constitutive secretory pathways to perform their functions. Understanding how membrane trafficking and secretion are coupled to other cellular functions like growth, which is also thought to be linked to secretory and endocytic functions, is fundamental to cell biology and to certain pathologies such as diabetes and cancer. During my DPhil, I have been developing the secondary cells (SCs), which reside in the male Drosophila accessory gland, as a new in vivo system to dissect out the genetic regulation of membrane trafficking and its link to secretion and cell growth. SCs are epithelial cells located at the distal tip of each accessory gland. They contain a number of large intracellular compartments (>5 μm diameter) allowing membrane trafficking to be easily visualised. This in turn makes scoring specific trafficking phenotypes in normal and genetically manipulated cells very reliable. Using imaging of both live and fixed cells, I show that SC compartments have specific Rab signatures characteristic of both secretory and endolysosomal compartments. The late endosomal and lysosomal marker, Rab7, is predominantly found on acidic compartments whilst Rab11, a slow recycling endosomal marker, is localised on the membranes of about ten non-acidic compartments containing dense-core granules (DCGs) and the protease angiotensin-converting enzyme (ANCE). I show that Rab GTPases regulate the maturation and number of compartments, the secretion of intraluminal vesicles, called exosomes, and the growth of SCs. Rab11 and Rab7 appear to control the balance between large non-acidic and acidic compartments in SCs, while Rab35, which coats smaller fast-recycling endosomal compartments (~1 μm), also controls the number of these large compartments. BMP signalling regulates SC growth and membrane trafficking. Using knockdown experiments, I show that all components associated with BMP signalling are involved in this process. Interestingly, I demonstrate that as well as ANCE, Dpp, the fly homologue of mammalian BMP 2 and 4, is localised inside DCGs of SCs. Dpp is the predominant ligand controlling SC growth and exosome secretion via autocrine and paracrine mechanisms. Interestingly, mating elicits the secretion of DCG compartments (DCGs), a process dependent on the Synaptosomal-associated protein 24kDa, SNAP24. BMP pathway activation is also increased in a Dpp-dependent fashion, presumably as a result of Dpp secretion, and it accelerates the rate of DCG biogenesis. I propose a model in which Dpp regulates the replenishment of DCGs in response to release via an autocrine feedback loop.